Growth Modulation With Reconstruction Plate for Genu Valgum Deformity in Twins: A Case Report and Literature Review‌ - Salman Ghaffari; Parastoo Mohammad amini (Mazandaran University of Medical Sciences, 2020)
Genu valgum is an angular deformity caused by several reasons, such as congenital syndromes, post-traumatic bone dysplasia, or an idiopathic form. It generates cosmetic problems, difficulties in function, and pain. Manipulating the growth plate by hemiepiphysiodesis with implants helps to achieve the correct alignment. We presented twin girls diagnosed with genu valgum deformity who were suffering from cosmetic problems and pain. We used growth modulation to temporarily arrest the growth plate. This procedure was followed by photographs and after 8 months, the implants were removed without having overcorrection. A brief literature review was also performed concerning the reported cases in the international databases, such as PubMed and Google Scholar on growth modulation for genu valgum deformity in twins. Twin girls with genu valgum deformities underwent hemiepiphysiodesis surgeries. We used reconstruction plates and 3.5 mm non-cannulated screws to fix both the distal femur and proximal tibia to temporarily arrest the growth plate. When we achieved the correct alignment the devices were removed.